Pengaruh Media Busy Book Terhadap Kemampuan Bahasa pada Anak Usia Dini di TK ALIF MEDAN HELVETIA Tahun 2022 (Sekolah Tinggi Agama Buddha Nalanda, 2023)
According to the World Health Organization (WHO) in 2019, language development disorders worldwide had a fairly high incidence of 27.5%. In 2020, the Indonesian Ministry of Health reported that 0.4 million (16%) of Indonesian toddlers experienced developmental disorders. One of the problems in early childhood is language development disorders. Impaired speech and language development in children will result in impaired reading ability, verbal ability, behavior, psychosocial adjustment and poor academic ability. Efforts are needed to hone children's language skills by using interesting and fun methods and media to attract children's attention. The aim of this research is to determine the effect of busy books on the language skills of early childhood at Kindergarten Alif Medan Helvetia. The type of research used is pre-experimental design with a one group pretest-post test design. The sampling technique used the Slovin formula to obtain a sample size of 37 respondents in this research. The results of the study showed that the characteristics of the respondents were mostly female children (62.2%) and children aged 5 years (51.4%). Frequency distribution based on early childhood language abilities before being given busy book media (86.5%), while early childhood language abilities after being given busy book media (97.3%). There is a significant influence on the provision of busy book media on the language skills of early childhood at Kindergarten Alif Medan Helvetia in 2022 with p-value = 0.000 (p<0.05). It is hoped that schools and parents can use busy books as a learning tool to develop early childhood language skills.